Lifestyle, dietary habits and consumption pattern of male university students according to the frequency of commercial beverage consumptions - Kim, H.M., Daejin University, Pocheon, Republic of Korea; Han, S.N., Seoul National University, Seoul, Republic of Korea; Song, K.H., Myongji University, Yongin, Republic of Korea; Lee, H.M., Daejin University, Pocheon, Republic of Korea (Nutrition research and practice, 2011)
Because excessive consumption of sugar-sweetened beverages may reduce the quality of nutritional intake, this study examined the consumption patterns of commercial beverages, lifestyle, dietary habits, and perception of sweet taste. Participants were 407 male university students in Kyeonggido, Korea, and information was collected by self-administered questionnaire. Among them, 58 nonsmokers volunteered to participate in the taste test. Participants were divided into three groups according to the frequency of commercial beverage consumptions: 120 rare (less than 1 serving/week), 227 moderate (1-3 servings/week) and 133 frequent (greater than 3 servings/week) consumption groups. More subjects from the rare consumption group chose water, tea, and soy milk, and more from the frequent consumption group chose carbonated soft drinks and coffee (P=0.031) as their favorite drinks. Frequent consumption group consumed fruit juice, coffee, and sports and carbonated soft drinks significantly more often (P=0.002, P=0.000, P=0.000, respectively), but not milk and tea. Frequent consumption group consumed beverages casually without a specific occasion (P=0.000) than rare consumption group. Frequent drinking of commercial beverages was associated with frequent snacking (P=0.002), meal skipping (P=0.006), eating out (P=0.003), eating delivered foods (P=0.000), processed foods (P=0.001), and sweets (P=0.002), and drinking alcoholic beverages (P=0.029). Frequent consumption group tended to have a higher threshold of sweet taste without reaching statistical significance. The results provide information for developing strategies for evidence-based nutrition education program focusing on reducing consumption of unnecessary sugar-sweetened commercial beverages.